Urinary concentrations of PAH and VOC metabolites in marijuana users. (March 2016) - Wei, Binnian; Alwis, K. Udeni; Li, Zheng; Wang, Lanqing; Valentin-Blasini, Liza; Sosnoff, Connie S.; Xia, Yang; Conway, Kevin P.; Blount, Benjamin C.
Abstract: Background: Marijuana is seeing increased therapeutic use, and is the world's third most-popular recreational drug following alcohol and tobacco. This widening use poses increased exposure to potentially toxic combustion by-products from marijuana smoke and the potential for public health concerns. Objectives: To compare urinary metabolites of polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds (VOCs) among self-reported recent marijuana users and nonusers, while accounting for tobacco smoke exposure. Methods: Measurements of PAH and VOC metabolites in urine samples were combined with questionnaire data collected from participants in the National Health and Nutrition Examination Surveys (NHANES) from 2005 to 2012 in order to categorize participants (≥ 18 years) into exclusive recent marijuana users and nonusers. Adjusted geometric means (GMs) of urinary concentrations were computed for these groups using multiple regression analyses to adjust for potential confounders. Results: Adjusted GMs of many individual monohydroxy PAHs (OH-PAHs) were significantly higher in recent marijuana users than in nonusers ( p  < 0.05). Urinary thiocyanate ( p  < 0.001) and urinary concentrations of many VOC metabolites, including metabolites of acrylonitrile ( p  < 0.001) and acrylamide ( p  < 0.001), were significantly higher in recent marijuana users than in nonusers. Conclusions: We found elevated levels of biomarkers for potentially harmful chemicals among self-identified, recent marijuana users compared with nonusers. These findings suggest that further studies are needed to evaluate the potential health risks to humans from the exposure to these agents when smoking marijuana. Highlights: Urinary VOC and PAH metabolites were measured in recent marijuana users. Higher thiocyanate, acrylonitrile and acrylamide levels in marijuana users than nonusers The first examination to date of body burdens of VOCs and PAHs in marijuana users.